2020
DOI: 10.3390/met10080989
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Fe Content on the As-Cast Microstructures of Ti–6Al–4V–xFe Alloys

Abstract: In this work, the evolution of the solidification microstructures of Ti–6Al–4V–xFe (x = 0.1, 0.3, 0.5, 0.7, 0.9) alloys fabricated by levitation melting was studied by combined simulative and experimental methods. The growth of grains as well as the composition distribution mechanisms during the solidification process of the alloy are discussed. The segregation of the Fe element at the grain boundaries promotes the formation of a local composition supercooling zone, thus inhibiting the mobility of the solid–li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 20 publications
(24 reference statements)
1
1
0
Order By: Relevance
“…Random high angle GBs in Ti have been shown to be stabilized by the segregation of Fe in the substitutional sites [24]. Fe segregation has also been reported in commercial Ti alloys with no analysis of the influence of GB type on the segregation behaviour [69,25,70]. In the present study, Fe was observed to segregate preferentially in few selected symmetric facets in Σ13 (0001) Ti GB, as seen in Fig.…”
Section: Grain Boundary Segregationsupporting
confidence: 67%
“…Random high angle GBs in Ti have been shown to be stabilized by the segregation of Fe in the substitutional sites [24]. Fe segregation has also been reported in commercial Ti alloys with no analysis of the influence of GB type on the segregation behaviour [69,25,70]. In the present study, Fe was observed to segregate preferentially in few selected symmetric facets in Σ13 (0001) Ti GB, as seen in Fig.…”
Section: Grain Boundary Segregationsupporting
confidence: 67%
“…The advantages and disadvantages of such treatment were analyzed for expanding the database of possible β-Ti bio-alloys that could be used, depending on the specific requirements of different biomedical implant applications. Ding et al [8] evaluated the solidification microstructure of Ti-6Al-4V-xFe (x = 0.1, 0.3, 0.5, 0.7 and 0.9) alloys fabricated by levitation melting. The growth of grains in the function of Fe content, as well as the composition distribution mechanisms during the solidification process of the alloy, were discussed.…”
Section: Development Of Microstructure and Operational Propertiesmentioning
confidence: 99%